Organon – tracing the name of an unknown musical instrument in the Bible - Duev, Ratko (Živa Antika & The Faculty of Philosophy, Skopje, 2019)
Studies of the Old Testament musical instrument ugab have remained unclear to this day, as can be seen in translations of the Bible into all European languages. Research of written and archaeological evidence suggests the the term organon may denote a specific musical instrument – a sort of a long (narrow) flute.